(untitled) (Plant Tissue Culture and Biotechnology, 2022)
The present investigation was carried out to develop an efficient in vitro regeneration protocol for strawberry plant using leaf explants. The highest percentage of callus induction was obtained on MS medium supplemented with 2.0 mg/l BAP and 0.5mg/l IBA. The highest numbers of shoots were regenerated from the callus on MS medium supplemented with 2.0 mg/l BAP and 1.5mg/l IBA. In case of root induction, MS medium supplemented with 1 mg/l IBA was found to be most effective. Following the development of roots, the in vitro regenerated plantlets were successfully transplanted into soil. Plant Tissue Cult. & Biotech. 32(1): 67-75, 2022 (June)